Democratic allsorts - Russell, Julian; Gailey, Tony; 220 Productions (Oley, PA : Bullfrog Films, 1993)
Focuses on the work of Frances Moore Lappé, who says famine is caused not by a lack of food, but by a lack of democracy. Presents her efforts to prevent hunger and starvation by promoting democratic decision-making on an individual and global level
Copy in DVD Format
Edited by Ray Thomas
Narrated by Julie Kalya
VHS Format
Keywords: Lappe, Frances Moore; Democracy; Famines; Hunger; Starvation